A search algorithm optimization path planning in mobile robots scenarios - Lima, José; Costa, Pedro; Costa, Paulo; Eckert, Lucas; Piardi, Luis; Moreira, A. Paulo; Nakano, Alberto (AIP conference proceedings, 2019)
Path planning for mobile robotics in unknown environments or with moving obstacles requires re-planning paths based on information gathered from the surroundings. Moving obstacles and real time constraints require fast computing to navigate and make decisions in a mobile robot. This paper addresses an optimization approach to compute, with real time constraints, the optimal path for a mobile robot based on a dynamically simplified A* search algorithm with a commitment on the available time.